Pembentukan Badan Layanan Umum Daerah Oleh Pemerintah Daerah (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
The purpose of this study is to analyze the authority of the Regional Government in establishing the Regional Public Service Agency. This research is normative legal research with statutory and conceptual approaches. The results of this study found that based on Article 346 of Law No.23/2014 in conjunction with Article 205 paragraph (1) PP No.12/2019 Regional Government has attribution authority to form BLUDs with the aim of improving public services. The authority of the Regional Government to form a BLUD is a discretionary authority that gives the choice to the Regional Government whether or not to form a BLUD based on consideration and an assessment of regional needs to improve public services. In forming a BLUD, Regional Governments must meet the requirements as stipulated in Article 29 Permendagri No.79/2018, namely substantive, technical and administrative requirements. Keyword: authority; public service, regional government; regional public service agency Abstrak Tujuan penelitian ini adalah menganalisis kewenangan Pemda dalam pembentukan BLUD. Penelitian ini adalah penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian ini menemukan bahwa berdasarkan Pasal 346 UU No.23/2014 jo Pasal 205 ayat (1) PP No.12/2019 Pemda memiliki kewenangan atribusi untuk membentuk BLUD dengan tujuan untuk meningkatkan pelayanan publik. Kewenangan Pemda untuk membentuk BLUD merupakan kewenangan diskresi yang memberikan pilihan kepada Pemda untuk membentuk BLUD atau tidak berdasarkan pertimbangan dan penilaian kebutuhan daerah untuk meningkatkan pelayanan publik. Dalam pembentukan BLUD, Pemda harus memenuhi persyaratan sebagaimana ditentukan dalam Pasal 29 Permendagri No.79/2018 yakni persyaratan substantif, teknis, dan administratif. Kata kunci: badan layanan umum daerah; kewenangan; pelayanan publik; pemerintah daerah